Sevoflurane Induces Ferroptosis of Glioma Cells Through Activating the ATF4-CHAC1 Pathway - Xu, Yingyi; Zhang, Na; Chen, Cheng; Xu, Xinke; Luo, Ailing; Yan, Yaping; Lu, Yanhua; Liu, Jianhua; Ou, Xinxu; Tan, Yonghong; Liang, Yufeng; Chen, Lihe; et al. (Frontiers in Oncology, 2022)
Objective To clarify the function and mechanisms of sevoflurane (Sev) on ferroptosis in glioma cells. Methods Different concentrations of Sev were used to treat glioma cells U87 and U251. Ferroptosis inducer Erastin was used to incubate glioma cells combined with Sev and ATF4 siRNA transfection treatment. CCK-8 assay and colorimetric assay were performed to analyze cell viability and Fe+ concentration, respectively. The releases of reactive oxygen species (ROS) were determined by flow cytometry analysis. Transcriptional sequencing was used to screen the differential genes affected by Sev in U251 cells. The mRNA and protein expression of ferroptosis-associated genes was detected by qRT-PCR and Western blotting. Results Sev could suppress cell viability, increase ROS levels and Fe+ concentration, downregulate the protein expression levels of GPX4, and upregulate transferrin, ferritin, and Beclin-1 in a dose-dependent manner in U87 and U251 cells. The expression of ferroptosis and mitophagy-related gene activating transcription factor 4 (ATF4) was identified to be enhanced by Sev analyzed by transcriptional sequencing. ChaC glutathione-specific gamma-glutamylcyclotransferase 1 (CHAC1), which is involved in ferroptosis, is a downstream gene of ATF4. Inhibition of ATF4 could interrupt the expression of CHAC1 induced by Sev in U87 and U251 cells. Ferroptosis inducer Erastin treatment obviously inhibited the cell viability, elevated the Fe2+ concentration, and promoted ROS generation in U87 and U251 cells. The protein level of ATF4 and CHAC1 was increased in Erastin-treated U87 and U251 cells. Moreover, the interruption of Sev-induced ferroptosis and CHAC1 activating induced by ATF4 suppression could be reversed by Erastin. Conclusions In summary, this study suggested that Sev exposure-induced ferroptosis by the ATF4-CHAC1 pathway in glioma cells.